Chirality-controlled growth of single-walled carbon nanotubes via nanotube cloning - Kim, Myung Jong; Kang, JungHo; Park, Min (POLYMER SOC KOREA, 2014)
Single-walled carbon nanotubes (SWNTs) have been intensively studied in the last two decades due to their remarkable electronic, thermal, mechanical, and optical properties. The major hurdle toward electronic applications is the difficulty to control chirality that determines their electronic properties. Since metallic and semiconducting nanotubes are mixed in as-grown materials produced by general growth methods, either chirality selective growth or separation of SWNTs is essential to electronic applications such as armchair quantum wires, transparent electrodes, and thin film transistors. This review article focused on nanotube cloning with chirality-selective growth and also dealt with other efforts on type-selective (metallic or semiconducting) growth of SWNTs.
Keywords: PREFERENTIAL GROWTH; CONTINUED GROWTH; SEPARATION; GAS; ENRICHMENT; DIAMETER; CONDUCTIVITY; MECHANISM; LENGTH; ROPES